Risk experiences and risk management strategies of beginning entrepreneurs - Ariola, Ma. Heliza Gay C.
This study investigated the perceived risks and risk management strategies of entrepreneurs. It focused on the experiences of entrepreneurs during the pre-start-up and start-up stages of their business ventures. A sample of twelve entrepreneurs, who own start-up businesses, was purposely chose to participate in the study. In depth, interviews were conducted to gather information regarding the entrepreneurs' experiences of risks and the risk management strategies that they use. Data were analyzed using descriptive statistics and content analysis. Results show that the entrepreneurs experience four types of risks during the pre-start-up stage. These risks include operations-related risks, financial-related risks, family and social related risks and competition risks. Among these risks, operations-related risks were observed to be the most common. Operations-related risks include finding the perfect business location and hiring and training qualified employees. The risks that are experienced during the pre-start-up stage are carried over during the start-up stage since most of these have long term effects on the business as the owners. However, additional risks emerge during this stage including staff recruitment, training and management risks and product service risks. In general, the entrepreneurs perceive risks in a positive manner. They consider these risks as a normal part of the business venture. Some of them view these risks as challenge, and a learning or opportunity. However, few entrepreneurs also see these risks as an obstacle to the success of the business. The risk management strategies that the entrepreneurs use can be classified into general and specific risk management strategies. Planning and evaluating prior to decision making, optimism and learning from mistakes, and immediate action were the general risk-management strategies that the respondents use. Specific risk-management strategies applied include: developing sound operation practices, utilizing innovation and marketing, using effective personnel education and management practices, developing sound financial practices and establishing social networks. Overall, the study revealed that the entrepreneurs experience different types of risks during the pre-start-up stages of their businesses. Nonetheless, the rewards and benefits of becoming an entrepreneur as well as the risk management strategies available are sufficient for them to pursue ans succeed in their business. Recommendations for future research are provided at the end of this paper.